In vitro biological activities of a combination of Ha-rak remedy, Piper betle, and Garcinia mangostana for the treatment of atopic dermatitis - Ubonwan Saesiw; Arunporn Itharat; Srisopa Ruangnoo; Wichan Ketjinda; Kalyarut Phumlek; Pattama Sriumpai; Neal M. Davies (Research in Pharmaceutical Sciences)
Background and purpose: Ha-rak (HR), an equal-proportion combination of roots from Capparis micracantha DC., Clerodendrum petasites S. Moore., Ficus racemosa L., Harrisonia perforata (Blanco) Merr., and Tiliacora triandra (Colebr.) Diels, Piper betle L. (PB), and Garcinia mangostana L. (GM) are commonly used in traditional Thai medicine to treat skin diseases, including atopic dermatitis (AD). Combining three medicines in adjusted proportions can improve efficacy, reduce toxicity, and reduce medication. This study aimed to evaluate the anti-allergic, anti-inflammatory, antimicrobial, and cytotoxic activities of the ethanolic extracts of different combinations to analyze the relationship among elements, medicinal tastes, and biological activities. Experimental approach: The biological activities (anti-allergic, anti-inflammatory, and anti-microbial activities and cell viability) of ethanolic extracts of plants and their combinations in various proportions were evaluated, as well as the chemical content of the developed remedies using the HPLC technique. Findings/Results: HMB-123 was the most significantly effective combination for AD. HMB-123 reduced β-hexosaminidase release from RBL-2H3 cells to a greater extent than chlorpheniramine. HMB-123 significantly inhibited nitric oxide and TNF-α production in LPS-stimulated RAW 264.7 cells. HMB-123 demonstrated antibacterial activity against all tested bacteria and antifungal activity against Candida albicans. For single extract, PB exhibited the highest anti-fungal activity, while GM exhibited the highest anti-bacterial activity. Conclusion and implications: The combined extracts showed potential as an optimized remedy for AD. HMB-123 demonstrated the highest anti-allergic, anti-inflammatory, and antimicrobial activities, making it a promising development candidate for AD treatment. To confirm safety and efficacy, further pre-clinical and clinical testing is necessary.